2020
DOI: 10.1155/2020/3182928
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Carbon Tax on CO2Emissions of China’s Power Industry

Abstract: Based on the TIMES model, a system for CO2 emission reduction in China’s power industry is built in this paper. Four scenarios including different carbon tax levels are set up, simulating the CO2 emissions of China’s power industry in 2020–2050 by using scenario analysis method. The power consumption demand, primary energy consumption structure, CO2 emission characteristics, emission reduction potential, and cost of different carbon tax levels are quantitatively studied. In combination with the impact on China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(39 reference statements)
0
8
0
1
Order By: Relevance
“…Berdasarkan hasil penelitiannya, Yu et.al (2020) menyebutkan bahwa setiap tahunnya, permintaan listrik dan energi di China akan diperkirakan terus meningkat yang akhirnya akan membuat jumlah emisi akan ikut meningkat pula. Penerapan pajak karbon akan membantu pemerintah China untuk mengatasi permasalahan ini, dimana dengan diterapkannya pajak karbon maka emisi karbon di China dapat berkurang secara signifikan dan akan mencapai titik puncak (peak value) pada tahun 2030-2040 (Yu et al, 2020). Selain itu, Yu et.al (2020) juga menyebutkan bahwa kebijakan pajak karbon yang sebaiknya diterapkan adalah medium carbon tax level yang artinya menerapkan tarif pajak karbon yang tidak terlalu rendah dan tidak terlalu tinggi sehingga emisi dapat ditekan secara signifikan namun PDB China hanya mengalami sedikit penurunan.…”
Section: Penelitian Terdahuluunclassified
“…Berdasarkan hasil penelitiannya, Yu et.al (2020) menyebutkan bahwa setiap tahunnya, permintaan listrik dan energi di China akan diperkirakan terus meningkat yang akhirnya akan membuat jumlah emisi akan ikut meningkat pula. Penerapan pajak karbon akan membantu pemerintah China untuk mengatasi permasalahan ini, dimana dengan diterapkannya pajak karbon maka emisi karbon di China dapat berkurang secara signifikan dan akan mencapai titik puncak (peak value) pada tahun 2030-2040 (Yu et al, 2020). Selain itu, Yu et.al (2020) juga menyebutkan bahwa kebijakan pajak karbon yang sebaiknya diterapkan adalah medium carbon tax level yang artinya menerapkan tarif pajak karbon yang tidak terlalu rendah dan tidak terlalu tinggi sehingga emisi dapat ditekan secara signifikan namun PDB China hanya mengalami sedikit penurunan.…”
Section: Penelitian Terdahuluunclassified
“…Then, there is another view: the carbon tax will bring in some negative externalities itself, although it can restrain corporate emissions to a certain extent. Yu et al (2020) and Tian et al (2020) suggested that the higher carbon tax rate will cause negative effects on economic development. The research by Xu and Wei.…”
Section: Literature Review Of Carbon Decision Between the Government ...mentioning
confidence: 99%
“…Hg is enriched in fly ash and captured by the precipitator in the CFB boiler, and the ESP and WFGD are the control methods [32][33][34][35][36]. In the database, technical parameters and reaction mechanisms of each technology are obtained, such as unit energy savings, emissions reduction, investment operation and maintenance (O&M) cost, current penetration rate, and applicable conditions [37][38][39]. The emissions of SO 2 , NOx, PM 2.5 , and Hg in the process of fuel consumption can be calculated.…”
Section: Assumptionsmentioning
confidence: 99%